2005
DOI: 10.1016/j.femsle.2005.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Lipolytic activity fromHalobacteria: Screening and hydrolase production

Abstract: Strains of Halobacteria from an Algerian culture collection were screened for their lipolytic activity against p-nitrophenyl butyrate (PNPB) and p-nitrophenyl palmitate (PNPP). Most strains were active on both esters and 12% hydrolyzed olive oil. A strain identified as Natronococcus sp. was further studied. It grew optimally at 3.5 M NaCl, pH 8 and 40 degrees C. An increase in temperature shifted the optimum salt concentration range for growth from a wider range of 2-4 M, obtained at 25-30 degrees C, to a narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 38 publications
2
36
0
3
Order By: Relevance
“…The cultures were grown at 37°C for 12 days. Afterwards, the screening of lipolytic activity of the strains was monitored under UV light at 350 nm as orange halos appearing around the colonies [1,12]. The growth of the selected Wve isolates was determined by the increase in optical density at 600 nm, and lipolytic activity was routinely assayed during 7 days of culture period.…”
Section: Methodsmentioning
confidence: 99%
“…The cultures were grown at 37°C for 12 days. Afterwards, the screening of lipolytic activity of the strains was monitored under UV light at 350 nm as orange halos appearing around the colonies [1,12]. The growth of the selected Wve isolates was determined by the increase in optical density at 600 nm, and lipolytic activity was routinely assayed during 7 days of culture period.…”
Section: Methodsmentioning
confidence: 99%
“…Lin et al 12 found that glycerol (50 g L −1 ) was the best carbon source for lipolytic activity by Antrodia cinnamomea, obtaining an enzyme activity of 27 U L −1 . Bhatnagar et al, 23 working with halobacteria Natronococcus sp., found the highest lipolytic activity of 45 U L −1 at pH 7.5 and temperature in the range 35-40…”
Section: Central Composite Designs (Ccd)mentioning
confidence: 99%
“…The biotechnological applications of halophilic lipases and thioesterases have been reviewed recently [69]. Bhatnagar et al isolated 54 Halobacteria from a salt lake in the Algerian Sahara and screened 35 of these strains [70]. Among them, strain TC6 (belonging to the Natronococcus genus) was selected for further study.…”
Section: Esterases and Lipasesmentioning
confidence: 99%